The UNESCO Seal of Excellence for Handicrafts - Abdul Hamid Haji Pour Shoushtari (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2005)
The United Nations Educational, Scientific and Cultural Organization (UNESCO) promotes a wide range of activities to preserve and develop both traditional and contemporary crafts. This includes a ten - year plan of action for the development of crafts in the world ( 1990 - 2000), the annual UNESCO crafts prize to recognize the creative talents of craft producers, as well as programmes to identify and bestow on the world's most outstanding artisans the title of": Human Living Treasure." On the other hand, creativity is the humankinds most widely and evenly distributed resources. All people seek outlets for self - expression and have the capacity to create objects to uplift the spirit and enhance peoples lives.